ANALYSIS OF JURIDIS HOUSEHOLD CONTRACT HOUSE RENT (RUSUNAWA) IN ACCELERATION OF HOUSING SUPPLY FOR LOW-INCOME COMMUNITY - Erniwati Erniwati; Martin Roestamy (Magister Hukum Sekolah Pascasarjana Unida, 2017)
Identification of this research are: 1) How is the implementation of rental contract agreement of simple rental apartment (Rusunawa) in accelerating the provision of housing for Low-Income Society? 2) What is the effect of contract rent lease agreement for a simple rental apartment (Rusunawa) in accelerating the provision of housing for Low-Income Communities that is transferred to a third party ?. The research method used in this research is the normative juridical approach. The results of this research are: 1) Implementation of flats rental management conducted by the Provincial Government of DKI Jakarta, the lease agreement in the apartment unit starts with if there are prospective tenants who want to rent so he can apply as a prospective apartment dweller to the manager 2) The legal consequences of the lease agreement transferred to a third party for a simple rental apartment (Rusunawa), made by the provincial UPT Rusunawa have rights and obligations, as for the rights of the parties contained in the article in the lease agreement hire which has been determined by UPT Rusunawa, based on agreement made by UPT Rusunawa.Keywords: Lease contract, Rusunawa, Low Income Society